PENINGKATAN MINAT BELAJAR ANAK YATIM PIATU DI PANTI ASUHAN FAJAR HARAPAN KOTA PEKANBARU - Ardiya Ardiya; pahmi pahmi; wandi syahfutra; prih febtiningsih; siti niah; agungprasetyo wibowo (Jurnal Pengabdian UntukMu NegeRI, 2018)
Community service carried out at the Fajar Harapan Orphanage in Pekanbaru City aims to provide counseling in increasing learning interest in the orphanage of the Fajar Harapan orphanage. The main problems faced are the low learning interest of children in orphanages, low interest in learning and a less conducive learning environment. The low interest in learning of children at the Fajar Harapan Orphanage has resulted in their performance decreasing in school and this is of course a problem for children and caregivers in this orphanage. To achieve the objectives of this community service activity, the lecture and discussion methods were used. In addition, an appropriate strategy is needed to foster children's learning interest in this orphanage, namely strategies to improve performance in schools, strategies to foster children's interest in learning and strategies to build a conducive learning environment. PPM activities that have been carried out take place smoothly in accordance with the expected plan. The participants of the activity responded positively and thanked the executor for providing useful knowledge to the participants, namely the strategy to foster interest in learning in order to improve learning achievement. Therefore they hope that this activity will not stop, but this activity will continue in the future.